Normally-off p-GaN/AlGaN/GaN high-electron-mobility transistors using oxygen plasma treatment. (3rd April 2019) - Sun, Chi; Hao, Ronghui; Xu, Ning; He, Tao; Shi, Fengfeng; Yu, Guohao; Song, Liang; Huang, Zengli; Huang, Rong; Zhao, Yanfei; Wang, Rongxin; Cai, Yong; et al.
Abstract: We propose a method of oxygen plasma treatment to realize normally-off p-GaN/AlGaN/GaN high-electron-mobility transistors. The fabricated device features an oxide surface passivation layer and a high-resistivity GaN cap layer at the access region, both transformed from p-GaN by the oxygen plasma treatment technique. With optimized treatment conditions, a low sheet resistance of 682 Ω/□ has been successfully obtained and the fabricated device shows high performance with a positive threshold voltage of +1.02 V, a maximum drain current of 301 mA mm −1, a high on/off ratio of ∼10 8, a breakdown voltage of 660 V, and low current collapse.